2020
DOI: 10.3171/2020.5.jns193264
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven model to identify high-risk aneurysms and guide management decisions: the Rupture Resemblance Score

Abstract: OBJECTIVEPrevious studies have found that ruptured intracranial aneurysms (RIAs) have distinct morphological and hemodynamic characteristics, including higher size ratio and oscillatory shear index and lower wall shear stress. Unruptured intracranial aneurysms (UIAs) that possess similar characteristics to RIAs may be at a higher risk of rupture than those UIAs that do not. The authors previously developed the Rupture Resemblance Score (RRS), a data-driven computer model that can objectively gauge the similari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A logistic regression model can be developed based on the differences of morphologic and hemodynamic parameters including SR, WSS, and OSI between ruptured and unruptured IAs ( 46 ). The model has also been used to predict the rupture probability of unruptured aneurysms, thus measuring their similarity to ruptured aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…A logistic regression model can be developed based on the differences of morphologic and hemodynamic parameters including SR, WSS, and OSI between ruptured and unruptured IAs ( 46 ). The model has also been used to predict the rupture probability of unruptured aneurysms, thus measuring their similarity to ruptured aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Upon detection of an unruptured IA, the next step is to determine whether surgical intervention is indicated. While no clear consensus hitherto exists, there are scoring systems such as the PHASES score, Ruptured Resemblance Score (RRS), and ELAPSS score which can guide clinical judgment (Greving et al, 2014;Thompson et al, 2015;Backes et al, 2017;Rajabzadeh-Oghaz et al, 2020). The PHASES score provides risks of IA rupture based on the following: population ethnicity, hypertension, age, size of aneurysm, earlier subarachnoid hemorrhage (SAH) from another IA, and site of IA.…”
Section: The Role Of Ai In Determining Aneurysm Rupture Risk and Prog...mentioning
confidence: 99%
“…These metrics were used, along with aneurysm SR, to calculate RRS for each case. High-risk cases were defined using size and RRS as: IAs with size greater than 5 mm [21], and IAs with an RRS greater than 30% [10,12] in their respective analysis.…”
Section: Image-based Computational Fluid Dynamicsmentioning
confidence: 99%
“…Hemodynamics is a key factor that drives IA pathophysiology, playing a critical role in aneurysm initiation, growth and rupture [9]. Studies using three-dimensional imaging and computational fluid dynamics (CFD) have identified and demonstrated the clinical utility of hemodynamic metrics associated with ruptured IAs [10,11]. For example, one such metric developed was rupture resemblance score (RRS), a multivariate logistic regression model based on size ratio (SR), normalized wall shear stress (WSS) and oscillatory shear index (OSI) that could accurately identify ruptured aneurysms with a sensitivity of 90% [12].…”
Section: Introductionmentioning
confidence: 99%